Application and Properties of Chicken Feather Fiber (CFF) a Livestock Waste in Composite Material Development - Bansal, Gagan; Gupta, Tushar; Singh, V. K.; Gope, P. C. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976783);" role="presentation">Rapid advancement in the field of Natural and <span dir="ltr" style="left: calc(var(--scale-factor)*274.01px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934874);" role="presentation">biomaterial <span dir="ltr" style="left: calc(var(--scale-factor)*323.95px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909391);" role="presentation">composites have <span dir="ltr" style="left: calc(var(--scale-factor)*396.31px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908035);" role="presentation">directed <span dir="ltr" style="left: calc(var(--scale-factor)*432.94px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988643);" role="presentation">in the <span dir="ltr" style="left: calc(var(--scale-factor)*461.38px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892228);" role="presentation">enlargement <span dir="ltr" style="left: calc(var(--scale-factor)*515.14px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91225);" role="presentation">various <span dir="ltr" style="left: calc(var(--scale-factor)*104.30px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940704);" role="presentation">innovative <span dir="ltr" style="left: calc(var(--scale-factor)*149.66px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914306);" role="presentation">materials and products which are <span dir="ltr" style="left: calc(var(--scale-factor)*286.49px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.863019);" role="presentation">eco-<span dir="ltr" style="left: calc(var(--scale-factor)*303.67px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987005);" role="presentation">friendly <span dir="ltr" style="left: calc(var(--scale-factor)*338.23px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915592);" role="presentation">as well as biodegradable. Importance is being <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938817);" role="presentation">given by <span dir="ltr" style="left: calc(var(--scale-factor)*109.46px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908094);" role="presentation">many <span dir="ltr" style="left: calc(var(--scale-factor)*134.06px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906505);" role="presentation">researchers to the natural plant fibers like <span dir="ltr" style="left: calc(var(--scale-factor)*302.59px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925059);" role="presentation">bamboo, coir, <span dir="ltr" style="left: calc(var(--scale-factor)*360.55px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927766);" role="presentation">jute, <span dir="ltr" style="left: calc(var(--scale-factor)*380.71px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900424);" role="presentation">sisal, cotton, wheat straw and <span dir="ltr" style="left: calc(var(--scale-factor)*501.34px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92405);" role="presentation">wood <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977662);" role="presentation">etc. Here the review based information is pileup to get the <span dir="ltr" style="left: calc(var(--scale-factor)*325.15px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942018);" role="presentation">wide-<span dir="ltr" style="left: calc(var(--scale-factor)*347.71px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921367);" role="presentation">ranging <span dir="ltr" style="left: calc(var(--scale-factor)*382.51px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958943);" role="presentation">information about the Mechanical <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908533);" role="presentation">properties, Physical properties, <span dir="ltr" style="left: calc(var(--scale-factor)*199.25px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91545);" role="presentation">Thermal properties etc. of Chicken Feather Fiber (CFF) based Composites. Also <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919414);" role="presentation">the application and making of different CFF based composites for industrial application and the use of CFF as a <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922367);" role="presentation">matrix, as a reinforced material and as a particulate. The efforts <span dir="ltr" style="left: calc(var(--scale-factor)*333.07px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90736);" role="presentation">are made to focus on <span dir="ltr" style="left: calc(var(--scale-factor)*421.06px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870578);" role="presentation">advanced <span dir="ltr" style="left: calc(var(--scale-factor)*461.74px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912865);" role="presentation">technology and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*413.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95716);" role="presentation">uplift the use of CFF as a Natural <span dir="ltr" style="left: calc(var(--scale-factor)*215.57px); top: calc(var(--scale-factor)*413.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94602);" role="presentation">Biomaterial <span dir="ltr" style="left: calc(var(--scale-factor)*266.33px); top: calc(var(--scale-factor)*413.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944715);" role="presentation">which is at present serve as a waste of poultry industry and to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*427.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900101);" role="presentation">enhance the use of livestock waste in a sustainable growth of the <span dir="ltr" style="left: calc(var(--scale-factor)*333.07px); top: calc(var(--scale-factor)*427.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904703);" role="presentation">earth and healthy environment.